(untitled) (Research, Society and Development, 2022)
Amor Island (Alter do Chão, Santarém, Pará, Brazil) is considered a region of great natural beauty and a national and international tourist attraction. The aim of this study was to determine the composition and density of the phytoplankton of the Amor Island, with emphasis on heterocytous cyanobacteria. Water samples for phytoplankton were collected and analyzed at seven points in October 2021. Filaments of heterocytous cyanobacteria were cultured and analyzed, measuring the cells of the first 30 trichomes. The abundance, diversity and evenness of phytoplankton species were calculated and balneability of beach in relation to algal blooms was evaluated. 106 generic and infrageneric taxa were identified, highlighting the Chlorophyta. Phytoplankton density was higher at Verde Lake (145.6 ± 22.0 org.L-1), diversity and evenness were higher at point 03 (Lake Verde) with 3.0 bits.cell-1 and 0.47, respectively. The most abundant species were: Aphanothece minutissima, Ankistrodesmus sp., Aphanothece sp., Aphanizomenon sp., Mougeotia sp., Merismopedia sp. and Quadrigula sp. The average density of cyanobacteria was higher in the Tapajós River (517.0 cell.mL-1). No algal and cyanobacterial blooms were identified, indicating water appropriate for bathing. Through morphological and morphometric description, the cultivated species were identified as Aphanizomenon gracile and Cylindrospermopsis/Raphidiopsis raciborskii, cited among the cyanobacteria with the highest occurrence of toxic blooms in the world. The region deserves phytoplankton monitoring studies, due to reports of cyanobacterial blooms, and greater knowledge of its planktonic biodiversity, since it is a threatened region.